Strategic Alignment to Net-zero Green Building Construction: Evaluating UAE Laws and Proposing International Benchmarks - ALHOSANI, MARIAM IBRAHIM (2024)
This dissertation explored the legal frameworks, regulations, and standards governing net-zero green building construction with a particular emphasis on the United Arab Emirates (UAE). Employing a comparative analysis, the study encompassed both international and regional laws, regulations, and standards from the United Kingdom (UK) and the United States (US) where relevant. In the UAE, attention is directed towards the Federal Environmental Law, Federal Civil Transactions Law, Administrative Resolutions, governmental policies, the Al Sa'fat regulations, and the Estidama rating system. In the UK, the exploration encompassed the Building Act 1984, Building Regulations 2010, Code for Sustainable Homes, and the Building Research Establishment's Environmental Assessment Method (BREEAM). On the other hand, the US search included the California Green Building Standard Code, Leadership in Energy and Environmental Design (LEED), International Green Construction Code (IgCC), and American Society for Testing and Materials (ASTM). The research findings highlighted the importance of the enforcement mechanism including issuing green construction-related laws and standards, and defining the non-compliance criteria and consequences. Moreover, the technical aspects addressed in this research within the fields of engineering and environment revealed limitations in existing standards, particularly in CO2 emission compliance urging the need for more robust and comprehensive guidelines. Recommendations include strengthening regulations, revising environmental laws, and adding provisions to the Civil Transactions Law. Further, the importance of a dedicated budget and employing green development strategies are stressed, proposing the enhancement of financial incentives and training programmes to encourage compliance with green construction standards. Overall, the dissertation advocates for a more integrated approach to enhance the legal framework to reach net-zero emissions in the construction sector in the UAE.